The impact of artificial intelligence on financial auditing: the case of Algeria - Amira Benachour; Ramzi Kaddai; Hanane Abdelmalek; Fella Bochelgoum; Lamine Tarhlissia (Менеджмент та підприємництво: тренди розвитку, 2025)
This study explores the impact of Artificial Intelligence (AI) on financial auditing in the Algerian context, highlighting its adoption, challenges, and opportunities. To this end, a survey was conducted using a questionnaire distributed to Algerian chartered accountants, statutory auditors, financial auditors, as well as other relevant stakeholders such as former audit firm directors and professionals involved in financial verification and auditing processes in Algeria. This population represents a diverse and representative sample of financial audit professionals, whose perspectives and experiences are essential for assessing the impact of AI on their practices and profession.